1995
DOI: 10.1097/00000539-199508000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Differential Age Effects of Mean Arterial Pressure and Rewarming on Cognitive Dysfunction After Cardiac Surgery

Abstract: Central nervous system dysfunction is a common consequence of otherwise uncomplicated cardiac surgery. Many mechanisms have been postulated for the cognitive dysfunction that is part of these neurologic sequelae. The purpose of our investigation was to evaluate the effects of mean arterial pressure (MAP) during cardiopulmonary bypass (CPB) and the rate of rewarming on cognitive decline after cardiac surgery. Two hundred thirty-seven patients completed preoperative and predischarge neuropsychologic testing. MAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 18 publications
0
28
1
1
Order By: Relevance
“…Therefore, the higher incidence of neuropsychological impairment in patients with marked S j o 2 desaturation during rewarming may have been caused by abnormalities in flow/metabolism coupling and/or brain pathology that were present before rewarming, rather than desaturation that occurs during rewarming per se. In addition, Newman et al [67] reported that the rewarming speed had no independent effect on postoperative neuropsychological outcome. Similarly, S j o 2 desaturation had only a minor independent effect on neuropsychological outcome when baseline neuropsychological status, educational level and age are considered.…”
Section: Cerebral Oxygenation and Cognitive Function After Cardiopulmmentioning
confidence: 99%
“…Therefore, the higher incidence of neuropsychological impairment in patients with marked S j o 2 desaturation during rewarming may have been caused by abnormalities in flow/metabolism coupling and/or brain pathology that were present before rewarming, rather than desaturation that occurs during rewarming per se. In addition, Newman et al [67] reported that the rewarming speed had no independent effect on postoperative neuropsychological outcome. Similarly, S j o 2 desaturation had only a minor independent effect on neuropsychological outcome when baseline neuropsychological status, educational level and age are considered.…”
Section: Cerebral Oxygenation and Cognitive Function After Cardiopulmmentioning
confidence: 99%
“…Recent reports from Duke University demonstrated that a reduction in SjvO 2 value had only a minor effect on neuropsychologic outcome. 15 However, Goto et alreported that a reduction in SjvO 2 in patients with preexisting neurological disorder may have great influence on neurologic outcome. 16 We did not examine neurological outcome in patients treated by normothermic CPB.…”
Section: Study Limitationsmentioning
confidence: 99%
“…min ¹1 ) infusions [5,6]. After tracheal intubation a triple-lumen central venous catheter and a pulmonary artery catheter were inserted via the right internal jugular vein.…”
Section: ¹1mentioning
confidence: 99%